The analytic hierarchy process: application to the election of the Chief Minister of Perak, Malaysia 2013 - Peredaryenko, Margarita Sergeevna; Mohamed Ariff, Rais Hussin (International Symposium on the Analytic Hierarchy Process (ISAHP), 2013)
For the last two-three decades in an attempt to predict most likely outcomes of public elections different methods and techniques have been developed and employed by social scientists to produce empirical evidence of a predictive power. This study is focusing on application of analytic hierarchy process (AHP) as a tool to forecast most likely winning candidate in the forthcoming election of the Chief Minister of Perak, Malaysia, in the year 2012. Two candidates, Dato Seri Diraja Dr. Zambry Abd Kadir Zambry and Dato Seri Ir’ Mohammad Nizar Jamaluddin, were compared vis-à-vis using AHP technique against seven sub criteria, such as charisma, humility, integrity, party, nation-building, people engagement, leadership and experience. AHP questionnaires were distributed in Ipon, state of Perak, Malaysia. There were 30 respondents selected randomly. According to the overall results, Dr. Zambry is projected to be the favored candidate for the post of Chief Minister of Perak in the forthcoming election with 59.57 per cent of winning votes over his counterparty Nizar. However, differences existed in voting between the three races representing population of Malaysians. Although Malays and Indians have shown the unanimous support to Dr. Zambry with the voting scores of 66.98 per cent and 69.55 per cent respectively, Chinese have given their preference to Nizar (60.12 per cent over Zambry).